Strategic Management of Multiculturalism for Social Sustainability in Hospitality Services: The Case of Hotels in Athens - Michalis Skordoulis; Olga Patsatzi; Stavros Kalogiannidis; Christina Patitsa; Aristidis Papagrigoriou (Tourism and Hospitality)
This study seeks to determine how multicultural management affects the promotion of a healthy and efficient working climate in hotels in Athens. Specifically, it explores employees’ attitudes toward diversity and multiculturalism, the effects of multicultural communication on cooperation and interpersonal dynamics, as well as the overall effects on organizational outcomes. This study uses both quantitative and qualitative research methods through structured questionnaires on 242 employees from the units of the hotel. Descriptive statistics, ANOVA, and regression analysis were used to analyze the relationship between multicultural management practices and workplace efficiency. The findings show that positive employee experiences and attitudes toward multiculturalism improve the working environment. Multicultural communication enhances collaborative and conflict-solving skills, and efficient multicultural management enhances teamwork and organizational outcomes. Personal experiences and observations of multiculturalism also provide a lot of input to a positive work climate. Multicultural people management practices are imperative for enhancing productive organizational relations in the hospitality industry. Therefore, the issues of appreciating cultural differences, the ongoing diversity training, and helping the workers to overcome language barriers should be emphasized. Hotels should also ensure that diversity training, dialog, and polices are ongoing and clear. Further research should investigate the time-dependency of multicultural management on employee turnover and guest satisfaction, cultural differences in various regions and industries, and the impact of technology and remote work on multicultural team dynamics.